COMPONENT-LEVEL ANTIOXIDANT CONTRIBUTIONS AND THERMAL STABILITY OF Azadirachta indica, Mangifera indica AND Persea americana LEAF EXTRACTS USED IN A POLYHERBAL FORMULATION - Ebhohimen, Israel Ehizuelen; Idris, Abbas Omokhudu; Ayeni-Idris, Queen; Idiakheua, Onosolesena Dennis (FUDMA Journal of Sciences, 2025)
This study investigated the component-level antioxidant contributions of Azadirachta indica (AI), Mangifera indica (MI), and Persea americana (PA) leaf extracts, the components of a previously studied polyherbal formulation. The aim was to delineate the contribution of each extract to the overall antioxidant capacity and to evaluate the influence of heat treatment and concentration on their activities. The samples were divided into two groups: a fresh extract and a pre-heated extract (heated for 30 min at 80°C). The antioxidant activity was evaluated using spectrophotometric assays for DPPH radical scavenging activity and total antioxidant capacity of graded concentrations (10-1000 µg/ml) and thermal treatment of 100 µg/ml solutions of the extracts for 5, 10, 15 and 20 min at 80°C. Mangifera indica extract demonstrated a superior antioxidant activity in a concentration-dependent manner; for DPPH, the fresh extract significantly increased from 30.53 ± 2.93%  to 81.32 ± 1.22% (IC50 = 358.41 µg/ml) while the pre-heated extract increased from 30.53 ± 3.00% to 86.05 ± 2.29% (IC50 = 359.81 µg/ml). For AI, the IC50 values were 4329.27 µg/ml (fresh) and 2738.82 µg/ml (pre-heated), respectively. The TAC increased with the duration of heating in the fresh AI and MI extracts but varied in the pre-heated extracts. It was concentration-dependent in both fresh and pre-heated AI and MI. The findings indicate that antioxidant activity in the AI-MI-PA formulation depends on both extract composition and processing conditions, suggesting the need for optimised thermal handling to preserve bioactivity.
Keywords: Azadirachta indica; Mangifera indica; Persea Americana; Antioxidant activity; Polyherbal formulation